Validation of a FAST Model of the Statoil-hywind Demo Floating Wind Turbine. (September 2016) - Driscoll, Frederick; Jonkman, Jason; Robertson, Amy; Sirnivas, Senu; Skaare, Bjørn; Nielsen, Finn Gunnar
Abstract: To assess the accuracy of the National Renewable Energy Laboratory's (NREL's) FAST simulation tool for modeling the coupled response of floating offshore wind turbines under realistic open-ocean conditions, NREL developed a FAST model of the Statoil Hywind Demo floating offshore wind turbine, and validated simulation results against field measurements. Field data were provided by Statoil, which conducted a comprehensive test measurement campaign of its demonstration system, a 2.3-MW Siemens turbine mounted on a spar substructure deployed about 10 km off the island of Karmøy in Norway. A top-down approach was used to develop the FAST model, starting with modeling the blades and working down to the mooring system. Design data provided by Siemens and Statoil were used to specify the structural, aerodynamic, and dynamic properties. Measured wind speeds and wave spectra were used to develop the wind and wave conditions used in the model. The overall system performance and behavior were validated for eight sets of field measurements that span a wide range of operating conditions. The simulated controller response accurately reproduced the measured blade pitch and power. The structural and blade loads and spectra of platform motion agree well with the measured data.